Investigation of key success factors for open innovation and firm performance in Indian IT and ITeS industry: A Systematic Literature Review - et. al., Anjali Sharma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Information Technology is a growing industry in India. Currently it constitutes around 7.7% of India’s GDP and the contribution is expected to rise by another 2.3% leading to a 10% share by the year 2025. Broadly the Indian IT sector can be categorized into two. They are the IT services and the IT enabled Services (ITeS). The expansion of the Indian economy has also led to the developments within the country to a large extent. The workforce in the sector constitutes more than 4mn. This field has further more wide opportunities of growth in terms of open innovation and the performances of the firms. Our nation lags behind the other countries of the world in both the terms. Being a nation filled with talents, this is an issue of concern and hence need to be addressed. As a result, a SLR has been prepared to understand the factors responsible for the growth of inventions and breakthroughs in IT and ITES along with those reasons responsible for the performance of any firm. Further research can be done with special focus on the corresponding factors which will prove to be a fruitful one for the IT sector and the Indian economy as a whole.